(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The current study attempts to investigate the details, conditions, and factors of the procedure of utilizing oil as a means, while some powerful politicians and governing circles, especially in Britain, getting the impression of the aim prospects of newly found political figures in Germany amongst the social-nationalists, attempted to apply them in their unattainable aims in regards with the legal characteristics of the Versailles Treaty. To meet that aim, a descriptive-analytical method is utilized and several related documents and sources are taken into account. Based on the results, the factual lack of its oil fields in the Weimar Republic and the oil supplies monopolization concerning executing a “legal mechanism for propelling Germany toward the East” facilitated controlling the Hitler regime’s foreign policy action to a particular point.